A move to majoritarian nationalism?: challenges of representation in South Asia - Adeney, Katharine (Taylor & Francis, 2015)
Despite India’s status as the world’s largest democracy and increasing turnouts in many of the countries of South Asia, recent elections raise concerns about the threat to democracy in the form of majoritarianism. Many of the countries of South Asia are extremely diverse and (mainly) informal mechanisms of accommodation of minorities have been deployed. At the same time concerns about the threat to minority rights in India, Pakistan and Sri Lanka have been strongly articulated. It is notable that those countries of South Asia, such as Sri Lanka and Pakistan, which have not accommodated their non-dominant groups, have witnessed high levels of conflict. India has been more accommodative, of both linguistic and religious minorities. However, it is precisely this process of accommodation that many in India now worry will be undermined by Hindu majoritarianism.